The Effectiveness of Castration And Seed Sources on the Growth and Production of Strawberry Plants (Fragaria x ananassa var duchesne) - Susilawati Hasibuan; Syahbudin Hasibuan; Ellen L. Panggabean (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Research on The Effectivity Of Castration And Seed Sources To The Growth And Production Of Strawberry Crops (Fragaria x ananassa var duchesne). Objectives to determine the effect of castration and seed sources in encouraging the growth and production of strawberry plants (Fragaria x ananassa var duchesne). The research was conducted at Fruit Plant Experiment Center of Berastagi Fruit Experiment Garden, Medan Berastagi road 60 kilometer, Karo district with ± 1200 meters above sea level. The study was conducted from May 2014 until August 2014, using Factorial Randomized Block Design (RAK), with four replications, 6 combinations to obtain 24 plant plots from all combinations and replications. The first factor to be tested was castration ie K0 = without castration, K1 = using castration. The second factor that tested is Source of seed of strawberry plant that is S1 = source of seed from seedling, S2 = source of seed from Sulur in book 1, S3 = source of seed from Sulur in book 2. The results showed that the castration was very significant in the observation of fruit weight of cultivation with 13.11 gram (K1S1) weight and no significant effect on production per plot, but the average yield of fruit weight per plot showed a high yield of 176.13 grams (K1S1). In general, this study showed castration treatment had an effect in increasing strawberry fruit weight to all sources of seeds